Relacje rynku turystycznego z rynkami substytucyjnymi - Aleksander Panasiuk (Ekonomiczne Problemy Usług, 2018)
The article presents the issues of substitutability of the tourism market with industry markets. The basic scope of substitution covers the tourism market with other leisure markets. At the outset, the issues of: the functioning and structure of the tourism market were presented. Next, the essence of substitutability of the tourist market was interpreted and the scope of its substitution with leisure markets was indicated and the characteristics of selected substitution markets were made. Other areas of substitutability in relation to the tourist market were also indicated. The basic effect of the analyzes carried out is the determination of three types of relationship between tourism market substitution and leisure markets. The aim of the study is to present the issue of substitution of the tourism market with other industry market, along with specifying the type of relations that take place between them.